Peningkatan Kapasitas Badan Usaha Milik Desa untuk Kesejahteraan Masyarakat - Abd. Rasyid Syamsuri; Julianto Hutasuhut (Universitas Prof. Dr. Hazairin, SH, 2020)
The Enhancement of Village Owned Business Agencies Capacity for Community Welfare Badan Usaha Milik Desa (BUMDes) aims to make village development innovations, especially improving the village economy and rural communities' welfare. BUMDes is a village business institution managed by the community and village government to strengthen the economy and is formed based on its needs and potential. Community service in Janji Village, Bilah Barat District, Labuhanbatu Regency was started by identifying the need for socialization: providing knowledge and understanding of the role of BUMDes and conducting focus group discussions based on interest groups in the village. The purpose of this program was to bring changes in the social-economic of the community. Based on the observations, partners' problems are: 1) The establishment of BUMDes in Janji Village has not fully formed all types of businesses in the area but has only formed one type of business, 2) There are objections from community members who already own home industry. As one of the economic institutions operating in rural areas, BUMDes must have differences from the general economic institutions so that the existence and performance of BUMDes can make a significant contribution in improving community welfare through socialization, education, and training to improve people's living standards in Janji Village.